Identificación y caracterización de la proteína del cuello de las roptrias 5 (RON5) en Plasmodium falciparum y determinación de las regiones de unión a glóbulos rojos humanos (2014)
In this research, advanced control strategies were designed under the Active Disturbance Rejection Control (ADRC) approach to increase the biomass production in microalgae cultures. For the above, from a control frame of reference, the development was envisaged into two stages, control and optimization. The first stage resulted in three different controllers designs: two ADRC strategies assisted by observer and a Model-Free Control (MFC). In each case, the aim was to guarantee the tracking of the reference signal. In the second stage, the design of two optimization strategies were achieves to increase the biomass production, offline and on-line. Comparing, at a simulation level, these strategies with other existing proposals, the following was found: 1) the ADRC strategies assisted by observer had a few dependence on the model, letting us to work with an approximate model that only required knowing of the system order and the input gain; 2) the off-line optimization, despite maximizing the biomass production, required knowing the model and 3) the proposal that combines MFC with on-line optimization, may act on any microalgae culture since it does not need a model. All the proposals are robust front to disturbances and variation of parameters allowing to increase the biomass production when an optimization strategy is used.